16 Delayed conduction and its implications in murine SCN5a+/− hearts: independent and interacting effects of genotype, age and sex. Issue 1 (10th December 2010) - Jeevaratnam, K; Tee, S P; Zhang, Y; Guzadhur, Y; Duehmke, R; Grace, A A; Lammers, W; Lei, M; Huang, C L H
Abstract : SCN5A haploinsufficiencies are implicated in clinical arrhythmic conditions associated with cardiac conduction disorders. We examined myocardial conduction and its dispersion, and relationships between them, in murine Scn5a+/– hearts modelling such clinical conditions. A 64- channel, multi-electrode array of electrode spacing 0.55-mm compared patterns of right ventricular activation in intrinsically beating Langendorff-perfused, male and female, and young (3 months) and old (>12-month-old), Scn5a+/− and WT hearts, from which monophasic action potentials were also obtained. Mean ventricular activation times (T*MEAN), spatial dispersions (D*S) between recording channels within a given cardiac cycle, and maximum activation times (T*MAX) representing the slowest possible conduction in any given heart were all higher in old male Scn5a+/– compared to young male and old female Scn5a+/– and old male WT. Temporal dispersions (D*T) of ventricular activation times at given recording channels were similarly higher in old male Scn5a+/– compared to old male WT. In contrast, T*MEAN, D*T, D*S and T*MAX were indistinguishable between all WT groups. All groupings of D*T, D*S and T*MAX gave linear correlations with T*MEAN, each with indistinguishable slopes. In contrast, measures of monophasic action potential duration were indistinguishable between all groups. Genotype, age and sex thus exert significant (p<0.05) independent and/or interacting effects on both myocardial conduction and its dispersion. These variates appeared to influence D*T, D*S and T*MAX through actions on T*MEAN. Effects on both myocardial conduction and dispersion were greatest in old male Scn5a+/– in direct parallel with features of the corresponding clinical arrhythmogenecity in Brugada Syndrome.